2000
DOI: 10.1007/s005400070016
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in pregnant women receiving aspirin and dipyridamole

Abstract: At the doses used in this study, aspirin and dipyridamole inhibited platelet aggregation for up to 3 days after cessation of medication. This abnormality of aggregation was not detected by the bleeding time and was not associated with clinically abnormal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…41 Kinouchi et al observed that ADP-induced platelet aggregation was decreased in pregnant patients receiving antiplatelet therapy (aspirin 40 mg/day + dipyridamole 150 mg/day), but remained within normal range; prothrombin times and PTT values were also not prolonged. 42 In the majority of cases, no special precautions are required for performing neuraxial anesthesia in patients receiving aspirin ( Table 2).…”
Section: Aspirinmentioning
confidence: 99%
“…41 Kinouchi et al observed that ADP-induced platelet aggregation was decreased in pregnant patients receiving antiplatelet therapy (aspirin 40 mg/day + dipyridamole 150 mg/day), but remained within normal range; prothrombin times and PTT values were also not prolonged. 42 In the majority of cases, no special precautions are required for performing neuraxial anesthesia in patients receiving aspirin ( Table 2).…”
Section: Aspirinmentioning
confidence: 99%
“…Adequate in vivo hemostasis as measured by thromboelastography has been reported in pregnant patients after aspirin ingestion (600 mg). 66 Kinouchi et al 67 found that ADP-induced platelet aggregation was decreased in pregnant patients receiving antiplatelet therapy (aspirin 40 mg per day þ dipyridamole 150 mg per day), but remained within a normal range; prothrombin time and APTT values were also not prolonged.…”
Section: Fondaparinuxmentioning
confidence: 99%